2002
DOI: 10.1046/j.1365-3059.2002.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar aggressiveness of Northern Ireland isolates ofPhytophthora infestanson detached leaflets of three potato cultivars

Abstract: The aggressiveness of 20 Northern Ireland single-lesion isolates of Phytophthora infestans was compared following their inoculation onto detached leaflets of three potato cultivars chosen on the basis of their differing levels of race-nonspecific resistance to late blight: Bintje (highly susceptible); Cara (moderately resistant); and Stirling (more resistant). Five isolates from outside Northern Ireland were included for comparative purposes: two from the Republic of Ireland; two from the USA (representing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 19 publications
(35 reference statements)
10
59
1
7
Order By: Relevance
“…The letters indicate significant differences between isolates (α05 %) Differences in aggressiveness among genetically close individuals have been obtained in other species with a relatively good level of confidence. In a very detailed study, Carlisle et al (2002) found differences in lesion expansion rate, latent period, spore production rate and infection efficiency among 17 P. infestans isolates, with nine replicates per isolate. These isolates shared an identical multilocus genotype (allozyme profiles), the same mating type, the same capacity to overcome the R1 specific resistance gene and the same sensitivity to a fungicide.…”
Section: Discussionmentioning
confidence: 99%
“…The letters indicate significant differences between isolates (α05 %) Differences in aggressiveness among genetically close individuals have been obtained in other species with a relatively good level of confidence. In a very detailed study, Carlisle et al (2002) found differences in lesion expansion rate, latent period, spore production rate and infection efficiency among 17 P. infestans isolates, with nine replicates per isolate. These isolates shared an identical multilocus genotype (allozyme profiles), the same mating type, the same capacity to overcome the R1 specific resistance gene and the same sensitivity to a fungicide.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies (Carlisle et al 2002;Day and Shattock 1997) have shown that new strains from culture are variable in their ability to infect and in their ability to sporulate on detached leaflets. However, the few comparisons that have been made of isolates of the old genotype with isolates of the new genotype have not shown clear evidence that new isolates were more 'aggressive'.…”
Section: Ukmentioning
confidence: 99%
“…James and Fry [23] did not observe local adaptation to partially resistant hosts since changes in pathogenic ability of the populations were not specific for the host on which the population was developed. In contrast, several reports have shown that P. infestans is capable of adaptation for virulence of partially resistant foliage and tubers [10][11][12]38,39]. Work by Andrivon et al [15] found that P. infestans populations adapted to the most locally dominant cultivar, regardless of the host resistance phenotype.…”
Section: Discussionmentioning
confidence: 96%